METHODS OF EFFICIENT MOTIVATION INCREASE FOR SWIMMING TRAINING PRACTICES - Andrej Simić; Elvis Vardo (Sport Scientific And Practical Aspects, 2025)
The aim of this paper was to examine the influence of goal setting interventions in combination with different kinds of feedback on swimming practice attendance. For this purpose, on a group od 16 respondents (swimmers), with the baseline period, two interventions were applied: goal setting with private feedback (first intervention) and goal setting with public posting (second intervention). By applying One – way repeated measures ANOVA and post hoc testing withBonferroni correction it was found that the attendance in the second intervention (M = 9.75; SD = 2.08) was significantly higher than in the baseline period (M = 7.69; SD = 2.02); t = 2.06, p < .01. Furthermore, the second and first intervention ((M = 8.19; SD = 2.61) also significantly differ in favour of the second intervention, ; t = 0.56, p = .042. No significant differences were found between the first intervention and baseline period. The results were explained with the benefits of public posting. Public posting enabled easier understanding of the goal concept, continous feedback, social comparion and social facilitation. These conditions endabled that respondent perceive the goal as important, that they accept it and put in effort in its achievement. This paper’s results have implications on coaching praxis.